2019
DOI: 10.3390/ma12142273
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polycaprolactone Modified Trimellitate Nano-Lubricant

Abstract: The application of trimellitate (TMT) in the lubricating oil industry was seriously restricted because of its low viscosity index. In the work reported here, polycaprolactone (PCL) soft chain was embedded into the structure of TMT in order to improve the viscosity index. Characterization of the polymers was done by proton nuclear magnetic resonance (1H-NMR), Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TG). Results supported our design and were consistent with the target prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Figure 2 d is the FTIR spectra of nanoprobes and IGF1 polypeptides. There is a sharp peak near 715 cm −1 in bTiO 2 -Gd-PDA, bTiO 2 -Gd-COOH, and bTiO 2 -Gd-IGF1, which is attributed to characteristic absorption peak of Ti–O [ 39 ]. After modified NH 2 -PEG-COOH through Michael addition reaction, bTiO 2 -Gd-COOH nanoprobes exhibit carboxylic acid symmetrical and asymmetrical stretching vibrations at 1386 cm −1 and 1573 cm −1 [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 d is the FTIR spectra of nanoprobes and IGF1 polypeptides. There is a sharp peak near 715 cm −1 in bTiO 2 -Gd-PDA, bTiO 2 -Gd-COOH, and bTiO 2 -Gd-IGF1, which is attributed to characteristic absorption peak of Ti–O [ 39 ]. After modified NH 2 -PEG-COOH through Michael addition reaction, bTiO 2 -Gd-COOH nanoprobes exhibit carboxylic acid symmetrical and asymmetrical stretching vibrations at 1386 cm −1 and 1573 cm −1 [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polycaprolactone (PCL) is a promising biopolymer from renewable sources synthesized by the ring-opening polymerization of ε-caprolactone (ε-CL) initiated by a suitable catalyst [1,2]. PCL is known for its exceptional biodegradability and flexibility and has attracted considerable attention in various fields such as food packaging, tissue engineering, wound dressings and drug delivery applications [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [18] evaluated the density, kinematic viscosity, viscosity index, friction reduction and anti-wear properties of gallate ester oils at 20 • C and pointed out that the physical or chemical adsorption film formed by gallate ester molecules between friction pairs was the key factor for their friction reduction and anti-wear properties. Guan et al [19] found that the modified nano-TMT base oil had excellent lubricating properties, good viscosity-temperature performance, thermal stability and anti-wear properties. Girma [20] analyzed the correlation between lubricant pressure-viscosity coefficients and molecular structure using the film thickness data of lubricants.…”
Section: Introductionmentioning
confidence: 99%